Contractual aspects of the organization of wages in Kazakhstan - Ydyrys, S.S.; Munasipova, M.E.; Junusbekov, M.M. (BUKETOV BUSINESS REVIEW, 2018)
The article deals with actual problems of wage on the basis of collective-contractual regulation. Particular attention is paid to the practice of setting parameters for labor payment in agreements of different levels (general, sectoral, regional). It is that the agreements contained in the General Agreement are binding for compliance with sectoral agreements. In turn, the conditions of work, employment and social guarantees, which are the subject of collective negotiations at the regional level, should not be worse than that established by sectoral agreements. Practice shows that the wage systems are in most cases developed and approved by employers only, without any involvement of employee representatives. Meanwhile, the legislation provides serious opportunities for employees to participate in the development of payment systems in the development of a collective agreement. This refers to the choice of wage systems as forms, the selection of the wage rate model, the determination of specific sizes of inter-digit and tariff coefficients, and, as a consequence, the values of the applied tariff rates and official salaries, the establishment of types and sizes of compensatory and incentive surcharges and wage surcharges. Based on analysis, proposals and recommendations on strengthening the role of collective-contractual regulation in determining the parameters of remuneration of employees.